Respuesta :

Answer:

option A, C , E

Step-by-step explanation:

- 4 + ( 4 + 5 ) = ( - 4 + 4 ) + 5      [ associative property ]

Answer:

A

C

E

Step-by-step explanation:

-4 + (4 + 5)

Using BEDMAS

Brackets

Exponents

Division

Multiplication

Addition

Subtraction

solve brackets first...

(4 + 5) = 9

9 - 4 = 5

A) (-4+4) + 5

   = (0) + 5

   = 5

B) (-4 - 4) + 5

   =(-8) + 5

   = - 3

C) -( 4 - 4) + 5

   = -(0) + 5

   = 5

D) - (4)+ ( -4) + 5

   = -4 + -4 + 5

   = -8 + 5

   = -3

E) -4 + 4 + 5

  =  0 + 5

  = 5